Phytoremediation of Heavy Metals in Contaminated Soils: A Review - Allamin, Ibrahim Alkali (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Heavy metals represent a major threat to public health and the environment if they are intentionally or unintentionally introduced into the soil. They are elements that cannot be degraded and can be teratogenic, mutagenic, and endocrine-disrupting. Carcinogens and toxins in humans can be caused by heavy metals, which are difficult to regulate. Phytoremediation has been recommended as an alternative to classic physicochemical remediation methods since it is more efficient for combating heavy metals pollution in soil or water bodies and ecologically friendly. Biomass produced as a result of phytoremediation can be utilised for cogeneration of energy and/or the creation of biofuels, all of which contribute to health, the environment, and cost-effectiveness. In order to improve the usage of phytoremediation in the coming years, a deeper understanding of the technique’s potential is necessary. Additionally, this study provides information on the use of herbaceous and woody plants for phytoremediation in soils affected by heavy metals.